Analisis Cara Berpikir Kritis Pada Hasil Belajar Matematika Siswa Berdasarkan Gender Kelas IV di SDN 2 Sutawinangun Kecamatan Kedawung Kabupaten Cirebon - Nabila; Reva Apriliani; Sanudin (GENFABET: Generasi Pendidikan Dasar, 2024)
This study aims to describe how critical thinking skills of students in mathematics in grade IV through a critical thinking ability test sheet consisting of 7 questions. This study was conducted at SDN 2 Sutawinangun in the odd semester of the 2022/2023 school year with all populations in the study being all grade IV students of SDN 2 Sutawinangun. The technique for data collection used was a test technique which was used to measure students' critical thinking skills on square and rectangle material. While for data analysis using qualitative descriptive analysis. Based on the results of the data analysis that have been obtained, the average percentage for the thinking skills of grade IV students is 78.26 and is in the sufficient category.